2019
DOI: 10.1101/648857
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Repetitive subconcussive head impacts and changes in sensory processing for balance control

Abstract: Background: Repetitive subconcussive head impacts (RHI) may be associated with current and future detrimental neurological effects. However, the effects of RHI on sensory processing for balance control is unknown and may have significant clinical implications if athletes are still participating in sport despite impairments. Research Question: Are there changes in sensory processing for balance control during standing and walking following RHI? Methods: Thirty healthy, adult, amateur soccer players (15 males, 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Of those studies, some have reported subtle acute effects of repetitive head impacts (e.g., following sparring 11 or heading drills in soccer 12,13 ), but these findings have been inconsistent. [14][15][16] The purpose of this study is to describe the frequency and magnitude of RHI through the course of a regular football season as a function of player position and practice activities and to examine the relationship between these impacts and acute (i.e., 24-hour and 1-week) and short-term (i.e., pre-season to post-season) changes in reaction time, balance, cognition, and symptoms in Division I collegiate athletes.…”
Section: Introductionmentioning
confidence: 99%
“…Of those studies, some have reported subtle acute effects of repetitive head impacts (e.g., following sparring 11 or heading drills in soccer 12,13 ), but these findings have been inconsistent. [14][15][16] The purpose of this study is to describe the frequency and magnitude of RHI through the course of a regular football season as a function of player position and practice activities and to examine the relationship between these impacts and acute (i.e., 24-hour and 1-week) and short-term (i.e., pre-season to post-season) changes in reaction time, balance, cognition, and symptoms in Division I collegiate athletes.…”
Section: Introductionmentioning
confidence: 99%
“…SRC vary in severity and clinical symptoms ranging from headaches and nausea to severe neurological impairments [2]. Research involving athletes who have sustained a SRC, have identified associated balance control deficits and highly variable actions when performing visuomotor processing tasks, such as dual tasks or perception-J o u r n a l P r e -p r o o f action coupling tasks, persisting well beyond the identified recovery period and return to sport [3][4][5][6][7][8][9][10][11][12][13][14][15]. Thus, physical symptom recovery post-SRC may not be indicative of absolute recovery leading to an increased likelihood of sustaining another concussion or injury during an everyday task [1,11,13,16], such as avoiding a collision with an object or approaching pedestrian.…”
Section: It Is Estimated That 38 Million Sports Related Concussions (...mentioning
confidence: 99%